PT BANK BTPN SYARIAH HEALTH LEVEL ANALYSIS IN THE PERIOD OF 2019 – 2021 - Muhammad Dhafi Iskandar; Ichksanto Wahyudi (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2024)
The Islamic banking industry continues to grow and develop, as evidenced by the increasing performance of Islamic banks that can meet the needs of society. One of the examples is PT Bank BTPN Syariah, a bank that focuses on providing financing to the micro sector. This study aims to evaluate the health of Bank BTPN Syariah using the CAMELS, RGEC, and Altman Z Score methods. The utilized data comes from financial reports from 2019 to 2021, and the applied method is quantitative descriptive. Literature that is relevant to the theme of this research is served to collect data. CAMELS (Capital, Asset Quality, Management, Equity, Liquidity, and Sensitivity Markets) is a data analysis technique used, followed by the RGEC method (Risk Profile, Good Corporate Governance, Equity, and Capital), and the Altman Z Score method. The results show that Bank BTPN Syariah was in a healthy position before and after the Covid-19 pandemic, by continuing to improve its performance and maximize its profits.